PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA MATERI BAGIAN TUMBUHAN DAN FUNGSINYA KELAS IV MI AL-ABRAR KOTA MAKASSAR - Yolanda Eunike Trihandayani; Ma’ruf Ma’ruf; Anisa Anisa (International Forum of Researchers and Lecturers, 2023)
This type of research is experimental research with a Quasy Experiment approach. The purpose of this study was to analyze the effect of the Make A Match learning model on student learning outcomes in science learning about plant parts and their functions for class IV MI Al-Abrar Makassar City. The total population in this study was 60 students. The sample used in this study was total sampling, namely 34 students in class IV A and 26 students in class IV B. The research design used is the Nonequivalent Control Group, which divides the class into two groups, namely the experimental class and the control class. The research procedure includes pretest, treatment, and posttest. The research instruments were observation sheets and learning achievement tests. Data collection techniques from this study were observation, tests (pretest-posttest) and documentation. The data analysis technique used is descriptive statistics and inferential statistics. The results showed that the hypothesis test using the t-test. The results of the study obtained tcount = 11.854, ttable = 2.918, so tcount>ttable or 11.854 > 2.918 and the sig (2-tailed) value was obtained 0.00, so 0.00 <0.05 was obtained. So it can be concluded that H0 is rejected, H1 is accepted. Based on the results of the research above, it can be concluded that there is an influence of the Make A Match learning model on student learning outcomes in science learning about plant parts and their functions for class IV MI Al-Abrar Makassar City.